The Effect of Organizational Culture, Digital Marketing Strategy, Service Quality, and Environmental Sustainability on Customer Satisfaction of MSME products in Indonesia - Loso Judijanto; Wendy Souisa; Arief Yanto Rukmana; Keni Kaniawati; Okta karneli (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2023)
This research investigates the various factors influencing customer satisfaction in Indonesia's context of Micro, Small, and Medium Enterprises (MSMEs). By examining the interaction between organizational culture, digital marketing strategy, service quality, and environmental sustainability, this study aims to explain how these elements collectively influence customer satisfaction. Data was collected from 300 Indonesian MSMEs and their customers and analyzed using Smart-PLS 4. The results showed a significant positive relationship between these factors and customer satisfaction. Organizational culture, digital marketing strategy, service quality, and environmental sustainability have different but interconnected roles in shaping customer satisfaction in Indonesian MSMEs. The findings provide valuable insights for MSMEs in Indonesia, showing that developing a customer-centric culture, implementing effective digital marketing strategies, maintaining high service quality standards, and integrating sustainability practices can improve customer satisfaction and contribute to business growth and competitiveness in this dynamic market.